On the usefulness of guidance reports - Mayew, William J.; Pinto, Jedson; Wu, Xiaoxi (Review of Accounting Studies, 2026)
We extract and describe corporate-issued guidance contained in over 23,000 LSEG Guidance Reports of S&P 1,500 firms from 2005 to 2021. Our sample contains 1.735 million Guidance Reports guidance instances that span over 180 guided items and fall into three broad categories: (1) qualitative topics, (2) consolidated financial statements, and (3) other key performance indicators. We identify research opportunities arising from Guidance Reports’ rich features, including quantitative or qualitative form, underpinning text, disclosure channels, and source speakers. We also compare Guidance Reports to the commonly used I/B/E/S Guidance database, which covers only quantitative guidance for 13 items. Approximately 1.494 million Guidance Reports instances fall outside I/B/E/S Guidance’s coverage, and even among overlapping items, only a subset is translated to I/B/E/S Guidance based on LSEG cost–benefit considerations. Our findings suggest researchers should be aware of the extent and nature of I/B/E/S Guidance omissions when studying guidance.